Cinderella ( Classic). (Pasig City : Viva Video, 2005)
Walt Disney's CINDERELLA, based on the world's greatest fairy tale, has captivated audiences for generations with its spellbinding story, memorable music, spectacular animation and unforgettable characters! Now, with an all-new digital restoration, CINDERELLA sparkles like never before! With a wave of her wand and some "Bibbidi-Bobbidi-Boo" Cinderella's Fairy Godmother transforms an ordinary pumpkins into a magnificent coach and Cinderella's rags into a gorgeous gown, then sends her off to the Royal Ball. But Cinderella's enchanted evening must end when the spell is broken at midnight. It will take the help of her daring animal friends Jaq and Gus and a perfect fit into a glass slipper to create the magic in this Special Edition of CINDERELLA and you, too, will believe that dreams really do come true.